Duration of dam contact had a long effect on calf rumen microbiota without affecting growth - Voland, Laurianne; Ortiz-Chura, Abimael; Tournayre, Jeremy; Martin, Bruno; Bouchon, Matthieu; Nicolao, Alessandra; Pomiès, Dominique; Morgavi, Diego P.; Popova, Milka (Frontiers in Veterinary Science, 2025)
IntroductionSeparating calves from their mothers at birth is linked to calf welfare issues and disturbances in the mother-calf relationship. It can also disrupt the maturation of the digestive tract, affecting calf health. It has been demonstrated that separation at weaning allows for the optimal establishment of the ruminal microbiota, whereas separation at birth alters colonization dynamics. We postulated that 4 weeks of cow-calf contact, a potentially more socially acceptable, and economically pragmatic, management practice, would induce a similar development of ruminal microbiota to that observed with separation at weaning, thereby conferring benefits on calf health and growth.MethodsWe studied three groups of 14 cow-calf pairs (Holstein and Montbéliarde breeds) with different cow-calf separation times: 4 weeks of contact with the mother (Mixed group), immediate separation (at birth, Control group) and delayed separation at weaning (11 weeks, Dam group). Rumen microbial colonization was monitored in 9 calves per group at 3, 10, 13, and 20 weeks of age using a metataxonomic approach. Body weight, diarrhea and respiratory disease were recorded to assess the calves' overall health. Serum IgG concentrations were also monitored.ResultsNo differences were observed between the groups in diarrhea or IgG concentration. The incidence of respiratory disease was lower in calves that remained in contact with their dams until weaning. After separation, the Mixed group exhibited an increased average daily gain. The metataxonomic analysis demonstrated that as calves aged, there was an increase in richness, accompanied by a corresponding increase in the number of shared microbial species over time between all groups. Nevertheless, three discrete development pathways were identified in the rumen bacterial communities, as evidenced by the differences in beta diversity between the groups over time. Additionally, the presence of the mother had a favorable effect on the transfer of beneficial microbiota during the early stages of life. However, this was offset by the elevated detection of potential pathogens at a later age in the Dam group.ConclusionIn this study, the rearing method exerted a profound and enduring influence on the gastrointestinal microbiota, with no discernible negative impact on health.